Dynamics of microbial community and changes of metabolites during production of type Ι sourdough steamed bread made by retarded sponge-dough method. (15th November 2020) - Wang, Xiangyu; Zhu, Xiaoge; Bi, Yanlan; Zhao, Renyong; Nie, Yuanyang; Yuan, Wenqiao
Highlights: Lactobacillus sanfranciscensis and Lactobacillus pontis were dominant bacteria. The dominant fungal species were Kazachstania humilis and Saccharomyces cerevisiae . A stable microbial consortia was established in sponge dough and main dough. Extended sponge retarding led to abundant volatile compounds with much more esters. Accumulation of organic acids and ethanol contributed to formation of ethyl esters. Abstract: Dynamics of microbial community and changes of metabolites during production of type Ι sourdough steamed bread made by retarded sponge-dough method (SSB) were studied. Lactobacillus sanfranciscensis and Lactobacillus pontis were the dominant bacterial species. Particularly, relative abundances of Lactobacillus sanfranciscensis were significantly higher than that of other sub-dominant bacterial species. The dominant fungal species were Saccharomyces cerevisiae and Kazachstania humilis, and the latter was the most predominant. A stable bacterial and fungal consortia was established in sponge dough retarded from 12 to 24 h and main dough proofed from 30 to 60 min. Metabolism preference for maltose of Lactobacillus sanfranciscensis favoured a mutualistic association with maltose-negative Kazachstania humilis, and hence contributing to their competitiveness and dominance. Volatile compounds became more abundant with much more esters as sponge retarding time extended. Probably, the accumulation of organic acids and ethanol contributed mostly to formation of ethyl esters in sponge dough during retarding.